Telecommunication project methods as an effective tool in modern education - Lebedeva, Marina; Beketov, Vladimir; Taranova, Marina (International Journal of Evaluation and Research in Education (IJERE), 2025)
This article is devoted to the study of the problem of insufficient involvement of philology students in the educational process, which negatively affects their academic performance. To solve this problem, a telecommunication project was developed and implemented to improve learning efficiency and student engagement. The research was based on a pilot project with one group, and survey methods were also utilized to measure the level of student engagement in the learning process. Statistical analysis results indicate a noticeable improvement in students’ academic performance after the implementation of the innovative telecommunication course, with the average score increasing from 75.5 to 80.1, supported by a statistically significant level. Survey data on student engagement demonstrate a high level of positive attitude towards the use of technology in the educational process. The overall trend indicates a positive attitude towards new technologies in education. The practical significance of this article lies in highlighting telecommunication project methods as an effective tool in modern education. Applying the results of this research in educational practice can contribute to the development and implementation of new educational programs based on telecommunication projects.